Delayed opposite frontal epidural hematoma due to bleeding from superior sagittal sinus with no cranial fracture – A case report - Sarkari, Avijit; Satyrathee, Gurudutta; Mahapatra, Ashok Kumar; Sharma, Bhawani Shankar (Indian Journal of Neurotrauma, 2012)
Extradural hematomas have a mortality of about 10%. If present in significant volume, they require urgent evacuation. Delayed extradural hematomas have similar significance. They are increasingly being diagnosed with routine use of CT scan. They may be formed after evacuation of contralateral hematoma and majority have associated cranial fractures. We report a case of delayed frontal epidural hematoma with superior sagittal sinus bleed, not associated with any skull fracture, formed after evacuation of a frontal convexity EDH.
Keywords: Extradural hematoma; Delayed; Bilateral; Sinus injury